2002
DOI: 10.1074/jbc.m207923200
|View full text |Cite
|
Sign up to set email alerts
|

Role of TRAF3 and -6 in the Activation of the NF-κB and JNK Pathways by X-linked Ectodermal Dysplasia Receptor

Abstract: X-linked ectodermal dysplasia receptor (XEDAR) is a recently isolated member of the tumor necrosis factor receptor family that has been shown to be highly expressed in ectodermal derivatives during embryonic development and binds to ectodysplasin-A2 (EDA-A2). By using a subclone of 293F cells with stable expression of XEDAR, we report that XEDAR activates the NF-B and JNK pathways in an EDA-A2-dependent fashion. Treatment with EDA-A2 leads to the recruitment of TRAF3 and -6 to the aggregated XEDAR complex, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 44 publications
5
70
0
Order By: Relevance
“…In addition, we found that XEDAR was a direct transcriptional target of p63, a member of the p53 family, which has an important role in epidermal development (data not shown). However, the evidence obtained so far (Sinha et al, 2002). On the other hand, the EDA-A2/ XEDAR pathway was also shown to promote apoptotic cell death through the DISC (death-inducing signaling complex) formation containing FADD, caspase-8, caspase-10 and c-FLIP (Sinha and Chaudhary, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, we found that XEDAR was a direct transcriptional target of p63, a member of the p53 family, which has an important role in epidermal development (data not shown). However, the evidence obtained so far (Sinha et al, 2002). On the other hand, the EDA-A2/ XEDAR pathway was also shown to promote apoptotic cell death through the DISC (death-inducing signaling complex) formation containing FADD, caspase-8, caspase-10 and c-FLIP (Sinha and Chaudhary, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…TRAF6 has been implicated in signaling via several receptors, including RANK (13,14), CD40 (53), IL-1R (18,54,55), TACI (56), BCMA (57), XEDAR (58,59), TROY (60), and CD14 (18). Several of these cytokines and lipopolysaccharide have been shown to induce apoptosis (61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase Reporter Assays-The NF-B reporter assay was performed essentially as described previously (14). Briefly, MEF cells were transfected in duplicate using LipofectAMINE 2000 (Invitrogen) in a 24-well plate with the various test plasmids along with an NF-B/ luciferase reporter construct (75 ng/well) and a Renilla luciferase reporter construct (phRG-TK; Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…C, increased NF-B transcriptional activity in MFF cells upon transient expression of vFLIP as measured by a luciferase-based reporter assay. MFF (wild type and NIKϪ/Ϫ) cells were transfected with an NF-B/luciferase reporter construct (75 ng/well) and a Renilla reporter construct (75 ng/well), and the experiment was performed as described previously (14). The values shown are the averages of one representative experiment of two in which each transfection was performed in duplicate.…”
Section: Fig 2 Nik Is Not Essential For Vflip K13-induced Nf-b Actimentioning
confidence: 99%